2021
DOI: 10.3390/foods10020409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extraction Buffer on the Solubility and Immunoreactivity of the Pacific Oyster Allergens

Abstract: Despite recent technological advances, novel allergenic protein discovery is limited by their low abundance, often due to specific physical characteristics restricting their recovery during the extraction process from various allergen sources. In this study, eight different extraction buffers were compared for their ability to recover proteins from Pacific oyster (Crassostrea gigas). The protein composition was investigated using high resolution mass spectrometry. The antibody IgE-reactivity of each extract wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
(54 reference statements)
3
14
0
Order By: Relevance
“…In this study, 21 patients were analysed for their IgE reactivity against the raw and cooked extract of the Pacific oyster. Similarly to the findings of previous studies [6,8], more IgE-binding proteins were observed in the raw compared to the heated protein extract. However, the heated extract demonstrated higher IgE binding intensity than the raw extract for the same IgE-binding proteins.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In this study, 21 patients were analysed for their IgE reactivity against the raw and cooked extract of the Pacific oyster. Similarly to the findings of previous studies [6,8], more IgE-binding proteins were observed in the raw compared to the heated protein extract. However, the heated extract demonstrated higher IgE binding intensity than the raw extract for the same IgE-binding proteins.…”
Section: Discussionsupporting
confidence: 86%
“…While food challenges are regarded as the gold standard of food allergy diagnosis, their application has been associated with risks of severe reaction in the case of shellfish challenge due to high allergen potency and adult patient co-morbidities [26]. Several mollusc IgE-reactive proteins have been identified in previous studies [6,8]. However, they have not been fully characterised, limiting their application as diagnostic tools for mollusc allergy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different extraction strategies should be conducted against different proteins’ properties to ensure their extractability. It is reported that a larger amount of IgE-reactive bands was observed from oyster when it was extracted using high-salt buffers or high-pH buffers [ 91 ]. The addition of 5 mM EDTA in the extraction solution increased salmon parvalbumin extractability significantly [ 23 ].…”
Section: Effect Of Processing On Fish Allergensmentioning
confidence: 99%